The Influence of Geology on Blasting Hazards and Results - T N. Little (The Australasian Institute of Mining and Metallurgy, 2011)
The aim of any rock breaking activity is to achieve success by developing designs that are blasting objective-specific and geology-specific, and then implementing such designs. This paper targets mining geologists with the aim of extending their knowledge of the rock fragmentation processes and providing insights to the significant relationships between geology and blasting. There are two main relationships, and if mining geologists appreciate both these relationships, then they can play a key role in optimising production. The business risk continuum is introduced to support this understanding. The first relationship is between geology and potential blasting hazards, and the operational complexity required to manage those risks. The risks associated with eight different ground types are discussed in terms of ground conditions, hazards and controls. These types are: reactive ground, hot ground, geothermal ground, fibrous ground, cavernous ground, combustible ground, pyritic ground and conductive ground.The second relationship is between the bench geology and blasting results. The blasting results discussed include: muckpile characteristics, remaining rock faces and blasting emissions. In this regard, some detailed insights and graphical examples are given for the influence of geology on blasting emissions, in particular, vibration, airblast and flyrock.A detailed description of the geological materials themselves can convey much useful information for blasting operators provided they are able to utilise this knowledge. Geologists are ideally suited to provide this description more effectively if they are familiar with the blasting process and the rock mass properties that influence blasting hazards and blasting results. It is also important to have clear statements of blasting objectives and associated operational targets, and this will maximise the likelihood of achieving the desired outcomes. The main aim of the paper is to highlight that geology is currently not fully utilised in the blasting process. In this regard, geologists are often not entirely aware of the blasting process and how they can contribute. The two significant relationships discussed above are integral parts of this process, and thus they are discussed as separate issues in the main body of this investigation.